CD23-Bound IgE augments and dominates recall responses through human Naive B cells - Griffith, Qyana K.; Onguru, Daniel O.; Mwinzi, Pauline N.; Ganley-Leal, Lisa M. (American association of immunology, 2010)
Human peripheral blood BCRμ+ B cells express high levels of CD23 and circulate preloaded with IgE. The Ag specificity of CD23-bound IgE presumably differs from the BCR and likely reflects the Ag-specific mix of free serum IgE. CD23-bound IgE is thought to enhance B Cell Ag presentation to T cells raising the question of how a B cell might respond when presented with a broad mix of Ags and CD23-bound IgE specificities. We recently reported that an increase in CD23+ B cells is associated with the development of resistance to schistosomiasis, highlighting the potential importance of CD23-bound IgE in mediating immunity. We sought to determine the relationship between BCR and CD23-bound IgE-mediated B cell activation in the context of schistosomiasis. We found that crude schistosome Ags downregulate basal B cell activation levels in individuals hyperexposed to infectious worms. Schistosome-specific IgE from resistant, occupationally exposed Kenyans recovered responses of B cells to schistosome Ag. Furthermore, cross-linking of CD23 overrode intracellular signals mediated via the BCR, illustrating its critical and dominating role in B cell activation. These results suggest that CD23-bound IgE augments and dominates recall responses through naive B cells.